THE ROLE OF TIKTOK @EVELYNHUTANI IN DISSEMINATING MULTICULTURAL DA’WAH AMONG GENERATION Z FROM JAMES BANKS’ PERSPECTIVE - nashikh, muhammad; firdaus, salsabil fadilah (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2025)
This study aims to examine the role of TikTok @evelynhutani in disseminating multicultural da'wah among Generation Z using James Banks’ multicultural education perspective. This research employs a qualitative approach with content analysis as its primary method. The data were collected through observation and documentation of two TikTok videos by Evelyn Hutani that showcase interfaith interactions within the context of religious diversity. The analysis was conducted using thematic analysis based on James Banks’ dimensions of multicultural education, including content integration, prejudice reduction, and equity pedagogy. The focus of this study is to explore how messages of tolerance and respect for religious differences are constructed and communicated in the selected content. The findings are expected to provide insights into how social media, particularly TikTok, can serve as an inclusive and relevant medium of da'wah for strengthening multicultural awareness among Generation Z in the digital age.